Critical Thinking for Social Justice in Global Geographical Learning in Schools. Issue 5 (3rd September 2019) - Kim, Gapcheol
Abstract: This study aims to theoretically investigate the notion of critical thinking for a more just understanding of self and "others" in global geographical learning. It focuses on the kinds of injustice in the world which are driven by our relationships with "others." By drawing on the literature of critical education, philosophy of education, and geography education, this study reveals how universal notions of criticality tend to easily undermine those perceived as global others and may highlight, in deficit mode, their perceived differences. Instead, the study presents the imperative of deconstructive thinking for a more just world. The article concludes by proposing a teaching strategy for alternative criticality which strives for justice in school geography.